YCH: Storage assignment in a unit-load warehouse - LIM, Yun Fong (Institutional Knowledge at Singapore Management University, 2016)
It is June 2014, and Lillian Lim of Mackor Consultancy, a third-party consultancy in Singapore, is at the newest warehouse of her client, YCH Group (YCH). Headquartered in Singapore, YCH is a major third-party logistics provider with business activities spanning across Asia. In 2012, YCH started construction of a US$159 million logistics hub that would use the latest supply-chain and logistics automation technology. Due to open in early 2015, the 1.5 million square feet of warehouse space and a million square feet of office space would house the YCH Group’s headquarters, as well as its research, training, and warehousing facilities. Lim’s company was hired to do a study on the improvements that could be made to increase the profitability of YCH’s warehouse operations at the hub. To do this, she needs to understand the expected pattern of supply and demand for goods at the warehouse, and the current process of storage and retrieval of inventory. Lim has to make a presentation on her preliminary findings in two weeks’ time to the Group’s senior management. This case can be used in undergraduate and graduate classes to illustrate the effectiveness of different policies for storage assignment in a unit-load warehouse. Students are expected to derive a suitable linear programming model to determine a storage assignment policy